Modeling the behavior of an industrial enterprise as a factor of sustainable development. (July 2020) - Fedorova, N V; Lobkov, K Yu; Tynchenko, S V; Eremeev, D V; Stupina, A A; Boyko, A A
Abstract: This article reveals the main factors affecting sustainability of organization's development, considers the basic concepts of the subject's behavior model in modern conditions of production organization, shows the basic components of modeling the enterprise's behavior in the enterprise system. The theoretical features of the enterprise's activity in modern conditions are considered, elements of the enterprise's development plan are listed and their brief description is given, conclusions are drawn. Also considered is the "4P" complex, which includes the "four policies": commodity, pricing, marketing and communication. Particular attention is paid to aspects of the practical application of this complex, which are manifested in the services sector, and the main means of influencing customers are considered. The main tasks and principles of the industrial enterprise. The concept of "8P" is also presented for consideration, its industrial orientation is justified. The use of this concept creates conditions for quick adaptation of production, assortment and quality of products, the entire system of managing the production and marketing activities of enterprises, determining the structure and dynamics of demand needs, performing individual tasks, which in turn ensure the achievement of the goal.